A group 13/group 17 analogue of CO and N2: coordinative trapping of the GaI molecule. - Coombs, N; Clegg, W; Thompson, A; Willock, D; Aldridge, S (2008)
The first row diatomic molecules N2 and CO have played central roles in developing fundamental models of electronic structure, and their interactions with transition metals have been widely investigated. By contrast, the valence isoelectronic molecules EX (E = group 13 element, X = group 17 element) have yet to be isolated under ambient conditions, either as the "free" molecule or as a simple metal complex. Here, we find that iodide abstraction from Cp*Fe(dppe)(GaI2) yields the stable complex [Cp*Fe(dppe)(GaI)]+ which features a terminally bound GaI ligand, characterized by a near linear (but readily deformed) Fe-Ga-I geometry and by very short Fe-Ga and Ga-I distances. Chemical and computational evidence reveal a relatively weak metal-ligand bond similar in strength to that found for dinitrogen analogues.